Does the form of venous thromboembolism prophylaxis following primary total knee arthroplasty alter the rate of early reoperation or revision surgery?. Issue 10 (24th June 2019) - Kerr, David L.; Butler, Stephen; Read, Andrew C.; Harris, Ian A.
Abstract : Background: Currently there is significant variation in the management of venous thromboembolism prophylaxis following total knee arthroplasty (TKA). Excessive wound ooze and bleeding is thought to increase a patient's risk of haematoma formation and possible infection. We evaluated the rate of unexpected reoperation in the perioperative period in patients who received aspirin, rivaroxaban or enoxaparin following primary TKA. Method: A systematic literature search was conducted in MEDLINE, CENTRAL and Embase to identify patients who underwent primary TKA. Two researchers independently reviewed the references identified in the literature search. The final 11 studies included for review were published between 1996 and 2016. Results: There was a higher rate of reoperation in patients treated with aspirin following TKA when compared to enoxaparin and rivaroxaban in the perioperative period. Of the 5141 patients treated with enoxaparin, 11 (0.21%) required reoperation; of the 2764 patients treated with rivaroxaban, 12 (0.43%) required reoperation; and of the 228 patients treated with aspirin, seven (3.07%) required reoperation. The average time to follow‐up in the 11 studies was 55 days, ranging from 30 to 180 days post‐operatively. Conclusion: There was a higher rate of reoperation in patients treated with aspirin following TKA when compared to enoxaparin and rivaroxaban in the perioperative period. While there is extensive data on the safety and efficacy of these medications following joint arthroplasty, improved reporting of surgically relevant outcomes are needed to assist both the surgeon and patient in clinical decision‐making. Abstract : Does the form of venous thromboembolism prophylaxis following primary total knee arthroplasty alter the rate of early reoperation or revision surgery: a systematic review and qualitative analysis.